A composite catalyst containing zinc pyridine carboxylate complex and its preparation method and application
The composite catalyst of zinc pyridine carboxylate and DMC addresses the limitations of existing catalysts by achieving high conversion rates and carbonate content in polypropylene carbonate production, ensuring high selectivity and activity, and shortening reaction times.
Patent Information
- Application Number
- CN202411362325.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Existing catalysts for polypropylene carbonate production face challenges in achieving high conversion rates and carbonate content simultaneously, leading to long reaction times, high energy consumption, and low production efficiency, while also posing safety risks due to high temperatures.
A composite catalyst comprising a zinc pyridine carboxylate complex and a double metal cyanide catalyst DMC, with a specific molar ratio and structure, enhances catalytic activity and selectivity, allowing for high carbonate content and conversion rates in low-temperature copolymerization reactions.
The composite catalyst achieves a propylene oxide conversion rate of over 95% with a polycarbonate content above 98% and a molecular weight distribution less than 1.5, significantly reducing reaction time and energy consumption, making it suitable for industrial production.
Smart Images

Figure CN118878808B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite catalysts, and in particular to a composite catalyst containing a zinc pyridinecarboxylate complex and a preparation method and application thereof. Background Art
[0002] Carbon dioxide (CO2) is an ideal synthetic carbon resource because it is abundant, renewable, cheap, non-toxic, and non-flammable. In recent years, the industrial production of aliphatic polycarbonates using CO2 has attracted widespread attention. In copolymerization reactions with epoxides, CO2 can be efficiently polymerized to synthesize polycarbonates. Polycarbonates have excellent properties: highly transparent, durable, biodegradable, and lightweight. Therefore, they have good applications in healthcare, food, and automotive industries.
[0003] Polypropylene carbonate (PPC) is a biodegradable polymer with "carbon fixation" function, which has the potential to alleviate the greenhouse effect and plastic crisis. It has good ductility, oxygen barrier and biocompatibility. In the preparation process of polypropylene carbonate (PPC), the existing industrial process mainly adopts heterogeneous catalysis, such as ternary rare earth catalysts, zinc carboxylate catalysts and bimetallic catalysts. However, the existing catalysts have poor catalytic activity and selectivity, resulting in poor quality of PPC products, low conversion rate and long reaction time, which limits its industrial production and application. Among them, the two most prominent problems are: (1) the problem of high conversion rate and high carbonate content of polypropylene carbonate cannot be taken into account; (2) the existing catalysts make the production process of polypropylene carbonate long, with the overall time taking more than 20 hours or even 40 hours, resulting in high energy consumption and low production efficiency.
[0004] Regarding question (1), in the preparation process of polypropylene carbonate (PPC), low temperature helps to increase the carbonate chain content in the product, but the conversion rate is low; high temperature helps to increase the conversion rate, but it is inevitably at the expense of reducing the carbonate chain content. Therefore, it has been impossible to achieve both high conversion rate and high carbonate content in polypropylene carbonate.
[0005] Specifically, in the heterogeneous catalytic polymerization process of polypropylene carbonate, the production of byproduct propylene carbonate (PC) is positively correlated with the reaction temperature, that is, the higher the PPC polymerization temperature, the higher the content of byproduct propylene carbonate (Chinese patent CN113185684B); at low temperatures, polypropylene carbonate can make the insertion of carbon dioxide more rapid and the conversion rate higher, but with the consumption of carbon dioxide, it will also cause part of propylene oxide to be continuously inserted, forming more polyether units, resulting in a lower carbonate chain content. As Chinese patent CN113185684B clearly reports, the reaction temperature for industrial preparation of PPC is generally controlled below 75°C, and in order to achieve a suitable conversion rate, the reaction time is generally controlled to be more than 10 hours. Despite this, the conversion rate of propylene oxide is only 30% to 40%. In addition, in order to improve the conversion rate, the Chinese patent CN114591501A uses a zinc carboxylate, a rare earth ternary catalyst or a bimetallic catalyst or a combination of at least two of them to prepare a composite catalyst for carbon dioxide polymerization. Under the high temperature and high pressure reaction conditions of 90°C and 8.0 MPa, the conversion rate of the composite catalyst is close to 100%, but at the same time, the polycarbonate content is less than 95%, and the molecular weight distribution is greater than 2. While the high conversion rate is obtained, the polycarbonate content and molecular weight distribution are greatly reduced. Similarly, in the Chinese patent CN101979424A, a composite catalyst is used to carry out copolymerization at a lower temperature of 60°C. Although the catalyst efficiency is increased to 550 g polyment / g cat , the propylene oxide conversion rate increased to 95%, but the carbonate chain content decreased to 68%, which still cannot take into account both high carbonate content and high conversion rate.
[0006] Regarding question (2), the poor activity of existing catalysts makes the entire production process of polypropylene carbonate long, with the total time taking mostly 20 hours or even 40 hours, resulting in high energy consumption and low production efficiency.
[0007] Polypropylene carbonate has a high viscosity. If the reaction is carried out at a high temperature, it is very easy to cause a temperature runaway phenomenon. In addition, the rapid reaction in a short period of time can easily cause the generated polypropylene carbonate to encapsulate the carbon dioxide required for the reaction, making it unable to continue to react with propylene oxide, resulting in a decrease in conversion rate. Therefore, in order to obtain a high carbonate content, reduce by-products and ensure the quality of PPC products, the reaction temperature of the existing industrial preparation of PPC is generally controlled below 75°C (CN113185684B), but the low reaction temperature and low catalytic activity of the catalyst result in a long production process time for PPC. For example, the zinc hydroxy acid complex catalyst in the Chinese patent CN101759849B is used to polymerize carbon dioxide and propylene oxide, with a polymerization temperature of 70°C and a polymerization time of up to 40 hours.
[0008] In summary, the existing polypropylene carbonate production process using heterogeneous catalytic polymerization still has two outstanding problems: (1) It is difficult to achieve both high conversion rate and high carbonate content of polypropylene carbonate; (2) In order to ensure production safety and product quality as well as lower production energy consumption, polypropylene carbonate is produced at a relatively low temperature below 75°C in the industry, but there are still problems such as long production process time, high energy consumption and low production efficiency, which seriously restricts industrial production and application. Summary of the invention
[0009] In view of the shortcomings of the prior art, the present invention provides a composite catalyst containing a zinc pyridine carboxylate complex and a preparation method and application thereof. The composite catalyst comprises a zinc pyridine carboxylate complex and a double metal cyanide catalyst DMC in a specific ratio and structure. The zinc pyridine carboxylate complex has both an electron-donating group and an electron-withdrawing group. The zinc pyridine carboxylate complex and DMC play a synergistic role after being composited. In the low-temperature (30-75°C) catalytic carbon dioxide copolymerization reaction, the composite catalyst has the characteristics of high selectivity and high activity. The high activity is reflected in that the catalytic activity can reach 480 g in 4 h. polyment / g cat The catalytic activity increased steadily or remained stable with the extension of polymerization time, and the catalytic activity could reach 510 g / mL in 12 h. polyment / g cat The selectivity is reflected in the fact that the polycarbonate content is above 98.0% and has a small molecular weight distribution, which is less than 1.5. On the basis of ensuring a high carbonate content, an extremely high propylene oxide conversion rate of more than 95% can be achieved, and the polymerization reaction time can be significantly shortened, so that the product has high carbonate content, high molecular weight, high conversion rate and low by-product content at the same time, which solves the problem that the prior art polypropylene carbonate cannot take into account both high conversion rate and high carbonate content, and solves the problem that the production process time is too long, and is very suitable for industrial production.
[0010] The technical solution of the present invention is as follows:
[0011] The present invention provides a composite catalyst containing a zinc pyridine carboxylate complex. The composite catalyst comprises a zinc pyridine carboxylate complex and a double metal cyanide catalyst DMC. The molar ratio of the zinc pyridine carboxylate complex to the double metal cyanide catalyst DMC is 1:1-60. The structural formula of the zinc pyridine carboxylate complex is shown in Formula 1:
[0012]
[0013] Formula 1,
[0014] Wherein, R1 is an electron withdrawing group selected from -CF3, -CN, -F, -Cl, -Br, -I; R2 is an electron donating group selected from -O-, -NHR3, -NH2, -OH, -OR4, -R5, -Ph, wherein R3, R4, R5 are any alkyl groups.
[0015] The composite catalyst of the present invention comprises a zinc pyridine carboxylate complex and a bimetallic cyanide catalyst DMC of a specific ratio and structure, a synergistic effect occurs between the bimetallic cyanide catalyst DMC and the zinc pyridine carboxylate complex, the bimetallic cyanide catalyst itself comprises the synergistic effect of two metals, and the introduction of the zinc pyridine carboxylate complex can further enhance the synergistic effect between cobalt and zinc, the electron transfer and interaction between different metals can improve the catalyst activity and selectivity, and the interaction between the metals is closely connected, and the tightness of this structure can reduce the structural change and agglomeration of the catalyst during the catalytic process, and the composite of the bimetallic catalyst and the zinc pyridine carboxylate complex can also form a more stable coordination environment, reducing the risk of deactivation of the catalyst due to ligand dissociation. Zinc pyridine carboxylate is an important component in the composite catalyst, and the N and O atoms in its ligand can form a stable complex with the zinc metal center, and in the process of composite with the bimetallic catalyst, there is electron transfer between cobalt, zinc metal and zinc pyridine carboxylate, and these electron transfer sites can affect the charge distribution and electronic structure of the catalyst, thereby improving the catalytic performance of the catalyst. In addition, a Zn-Zn bond with a bond length of 0.01 to 3.0 Å and a Zn-Co bond with a bond length of 0.1 to 5.0 Å are formed between the double metal cyanide catalyst component and the zinc pyridine carboxylate in the composite catalyst of the present invention. This bonding structure can produce unique catalytic performance, and can produce new reaction active sites in the electron transfer and spatial arrangement between different metals, thereby reducing the barriers between reactants and improving the reaction rate and selectivity. Therefore, due to the synergistic effect of the double metal cyanide catalyst DMC and the zinc pyridine carboxylate complex, the particle size of the composite catalyst of the present invention is reduced, the specific surface area is increased, more zinc active sites are exposed on the surface, and cobalt active sites are provided in the composite process. The combination of the two metal active sites makes it have higher catalytic activity, shortens the induction period of the copolymerization reaction of carbon dioxide and propylene oxide to 2 hours, and at a lower production process temperature, while improving the conversion rate of epoxy compounds, a polymer product with a high carbonate chain content and high thermal stability is obtained.
[0016] In one embodiment of the present invention, the average volume particle size of the composite catalyst is 10 nm to 16 nm;
[0017] In one embodiment of the present invention, the specific surface area of the composite catalyst is 16 m 2 / g~170 m 2 / g.
[0018] In one embodiment of the present invention, the composite catalyst has a Zn-Zn bond with a bond length of 0.01 to 3.0 Å and a Zn-Co bond with a bond length of 0.1 to 5.0 Å.
[0019] In one embodiment of the present invention, the composite catalyst has the following elemental composition by mass percentage: Zn 10-30%, Co 5-20%, C 30-40%, N 4-20%, O 10%-20%, and other substituent elements totaling 1-20%.
[0020] In one embodiment of the present invention, the double metal cyanide catalyst DMC has a structural formula of: Zn3[Co(CN)6]2:x ZnCl2•y t-BuOH·z H2O, wherein the x value ranges from 0.5 to 2.0, the y value ranges from 0.9 to 3.0, and the z value ranges from 1.0 to 3.5.
[0021] In one embodiment of the present invention, the molar ratio of the zinc pyridine carboxylate complex to the double metal cyanide catalyst is 1:5-30.
[0022] The present invention also provides a method for preparing a composite catalyst containing a zinc pyridine carboxylate complex as described above, wherein the zinc pyridine carboxylate complex, a double metal cyanide catalyst DMC and a mixed solvent are added to a high-pressure reactor at one time for dissolution, and the composite catalyst is prepared by a nitrogen / argon atmosphere reaction, wherein the mixed solvent is a mixed solvent comprising a polar solvent and a non-polar solvent; wherein the molar ratio of the zinc pyridine carboxylate complex to the double metal cyanide catalyst DMC is 1:1-60, the reaction temperature is 20-150°C, and the reaction time is 12-38 h; and the pressure of the nitrogen / argon atmosphere is 0.2-1 MPa;
[0023] The preparation method of the composite catalyst in the present invention is prepared by high temperature reaction by a high pressure reactor through a specific zinc pyridine carboxylate complex, a DMC catalyst, a polar solvent, and a non-polar solvent containing different functional groups. Specifically, in the preparation method of the present invention, a high pressure reactor is used to make the two metals in the zinc pyridine carboxylate and the bimetallic catalyst more easily form active sites under a high temperature nitrogen / argon environment, thereby exerting a synergistic effect, making the selectivity and activity of the catalyst higher, especially for two types of catalysts, the metals can be made to interact with each other under an argon / nitrogen gas atmosphere to be enhanced, improve the structural stability of the catalyst, and in the synthesis process, a high temperature environment is conducive to the synthesis of a stable catalyst product, and at the same time, an intermediate that is easily decomposed at high temperature can be stabilized under nitrogen atmosphere conditions, which is conducive to the synthesis of a composite catalyst. Compared with other preparation methods, the nitrogen / argon atmosphere reaction can obtain more delicate catalyst particles, a smaller catalyst particle size, and a more excellent synergistic effect, so that the catalyst has a more efficient and stable catalytic performance in subsequent polymerization reactions.
[0024] In one embodiment of the present invention, the dissolving is carried out by ultrasonic dissolving;
[0025] In one embodiment of the present invention, the volume ratio of the polar solvent to the non-polar solvent is 1:100-100:1; more preferably, the polar solvent is selected from one or more of water, acetonitrile, methanol, ethanol, acetone, isopropanol, acetic acid, and ether; more preferably, the non-polar solvent is selected from one or more of toluene, benzene, carbon tetrachloride, hexane, and dichloromethane;
[0026] In one embodiment of the present invention, after the nitrogen / argon atmosphere reaction, the suspension is cooled to room temperature, an organic solvent is added for filtration, and vacuum drying is performed to obtain the composite catalyst; more preferably, the organic solvent is selected from any one or more of ethyl acetate, ethanol, methanol, and dichloromethane; more preferably, the amount of the organic solvent is 2-20 times the volume of the suspension.
[0027] In one embodiment of the present invention, the preparation method of the zinc pyridine carboxylate complex is:
[0028] (1) dissolving a zinc source in dilute hydrochloric acid and stirring to obtain a zinc hydrochloric acid solution;
[0029] (2) dissolving a pyridine carboxylic acid containing an electron-withdrawing substituent and a pyridine carboxylic acid containing an electron-donating substituent in deionized water to form a pyridine carboxylic acid mixed solution;
[0030] (3) slowly adding the zinc hydrochloric acid solution dropwise to the pyridine carboxylic acid mixed solution to perform a reflux reaction;
[0031] (4) cooling, precipitating crystals, washing, and drying to obtain a zinc pyridinecarboxylate complex intermediate containing crystal water;
[0032] (5) removing crystal water from the zinc pyridine carboxylate complex intermediate at a high temperature of 110 to 150° C. to obtain the zinc pyridine carboxylate complex;
[0033] The zinc source is selected from any one of zinc chloride, zinc sulfate (ZnSO4), zinc chlorate [Zn(ClO3)2], zinc nitrate [Zn(NO3)2], zinc acetate [Zn(OAc)2], zinc oxide and zinc hydroxide;
[0034] The dilute hydrochloric acid refers to an aqueous solution of HCl with a pH value between 0 and 5; preferably, the pH value is between 3 and 5;
[0035] The electron-withdrawing substituent group is selected from -CF3, -CN, -F, -Cl, -Br, -I; preferably, the pyridine carboxylic acid containing an electron-withdrawing substituent group is selected from any one or more of 4-chloro-2,6-pyridinedicarboxylic acid, 4-bromo-2,6-pyridinedicarboxylic acid, 4-trifluoro-2,6-pyridinedicarboxylic acid, and 4-fluoro-2,6-pyridinedicarboxylic acid;
[0036] The electron-donating substituent group is selected from -O-, -NHR3, -NH2, -OH, -OR4, -R5, -Ph, wherein R3, R4, R5 are any alkyl groups; preferably, the pyridine carboxylic acid containing an electron-donating substituent group is selected from any one or more of 4-methyl-2,6-pyridinedicarboxylic acid, 4-ethyl-2,6-pyridinedicarboxylic acid, 4-ethoxy-2,6-pyridinedicarboxylic acid, 4-phenyl-2,6-pyridinedicarboxylic acid, and 4-methoxy-2,6-pyridinedicarboxylic acid;
[0037] The present invention forms a specific zinc precursor by selecting a zinc source treated with hydrochloric acid, and performs a reflux reaction with a mixed solution of pyridine carboxylic acids of two different electronic groups, and then adopts high temperature drying to obtain zinc pyridine carboxylate with two functional groups. The above unique preparation processes complement each other and are indispensable to form a synergistic effect, so that different pyridine carboxylic acids synthesize zinc pyridine carboxylate complexes with different functional groups. Specifically, in the preparation process of the present invention, the zinc source is firstly acidified to form a zinc hydrochloric acid solution. The zinc source is mostly insoluble in organic solvents. The solubility problem will be limited during the reaction of the zinc source and pyridine carboxylic acid. Therefore, the zinc source is firstly acid-treated, and the zinc source is corroded by an acidic medium to dissolve it into a soluble zinc salt, thereby improving its solubility; and in the process of chemical etching with dilute hydrochloric acid, a zinc salt film with a specific surface texture can be prepared, and the formation of this film is more conducive to the formation of the complex in the subsequent process, which can make the catalyst larger in specific surface area.
[0038] In the present invention, different electron groups are used to react with a zinc source to form a zinc pyridine carboxylate complex with different electron groups. The introduction of electron-donating and electron-withdrawing groups during the synthesis of the complex can significantly change the electronic structure of the zinc pyridine carboxylate complex, forming a diversified charge distribution and energy band structure. The nature of this electronic structure diversity can make the complex better compounded with a bimetallic catalyst, so that more active sites are exposed on the catalyst surface. The electron-donating group can enhance the electron density of the complex, while the electron-withdrawing group can adjust the charge distribution and the reactivity of the metal center. This dual regulation enables the complex to show higher activity and selectivity in the catalytic reaction. Reasonable electronic structure design can enhance the structural stability of the zinc pyridine carboxylate complex, so that it can maintain long-term activity during the catalytic process. In addition, the introduction of electron-donating and electron-withdrawing groups helps to reduce the decomposition or deactivation of the catalyst and improve its reuse. Due to the diversity of the electronic structure, the zinc pyridine carboxylate complex can achieve an efficient catalytic effect under milder reaction conditions. This characteristic not only reduces energy consumption and production costs, but also reduces the negative impact on the environment.
[0039] Therefore, the zinc pyridine carboxylate complex of the present invention uses a zinc source treated with hydrochloric acid to form a specific zinc precursor, which is subjected to a reflux reaction with a mixed solution of two pyridine carboxylic acids with different electron groups. The advantage of this is that zinc pyridine carboxylate with no pyridine carboxylic acid or zinc source residue on the surface, smaller grains, and completely exposed active sites is obtained, and high-temperature drying is performed to remove crystal water, thereby obtaining a more stable zinc pyridine carboxylate complex with a purity of up to 99.99%.
[0040] In one embodiment of the present invention, in step (1), the dissolving and stirring time is 1-2 h;
[0041] In one embodiment of the present invention, in step (1), the temperature of the dissolving and stirring is 10 to 50°C;
[0042] In one embodiment of the present invention, in step (1), the pH of the zinc hydrochloric acid solution is less than 6;
[0043] In one embodiment of the present invention, in step (2), the molar ratio of the electron donating group to the electron withdrawing group zinc pyridine carboxylate is 1:0.2-1:2; preferably 1:1;
[0044] In one embodiment of the present invention, in step (3), the molar ratio of the zinc hydrochloric acid solution to the pyridine carboxylic acid mixed solution is 1:1-20;
[0045] In one embodiment of the present invention, in step (3), the temperature of the reflux reaction is 50-150°C; more preferably, the temperature is 60-120°C;
[0046] In one embodiment of the present invention, in step (3), the reflux reaction time is 3-12 h; more preferably, the reflux reaction time is 6 h;
[0047] In one embodiment of the present invention, in step (3), the dripping speed is 5-50 drops / minute; more preferably, the dripping speed is 20-30 drops / minute;
[0048] In one embodiment of the present invention, in step (5), the temperature for removing the crystal water is 130-150°C.
[0049] The present invention also provides use of the composite catalyst as described above or the composite catalyst prepared by the preparation method as described above in preparing a copolymer of carbon dioxide and propylene oxide.
[0050] In one embodiment of the present invention, the composite catalyst is one or more of methyl-chloro-zinc pyridine carboxylate / DMC, bromo-ethoxy-zinc pyridine carboxylate / DMC, chloro-ethyl-zinc pyridine carboxylate / DMC, and bromo-methoxy-zinc pyridine carboxylate / DMC.
[0051] In one embodiment of the present invention, the method for preparing a copolymer of carbon dioxide and propylene oxide is as follows: adding a composite catalyst having a mass of 0.1 to 5% of the mass of the reaction monomer propylene oxide into a reactor, drying at 30 to 75°C for 2 to 24 hours under vacuum conditions, cooling to room temperature, adding purified propylene oxide, charging with carbon dioxide, making the pressure in the reactor reach 1.0-6.0 MPa, reacting continuously at 30 to 75°C and a stirring speed of 100 to 500 rpm for 4 to 12 hours, removing the reactor, cooling to room temperature, discharging unreacted carbon dioxide, taking out the product in the reactor, vacuum removing unreacted monomers, and washing the obtained product with a mixed solution of dichloromethane and methanol, and drying to obtain a copolymer of carbon dioxide and propylene oxide.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] The composite catalyst of the present invention comprises a zinc pyridine carboxylate complex and a double metal cyanide catalyst DMC in a specific ratio and structure. The double metal cyanide catalyst itself comprises the synergistic effect of two metals, and the introduction of the zinc pyridine dicarboxylate complex can further enhance the synergistic effect between cobalt and zinc. The electron transfer and interaction between different metals can improve the activity and selectivity of the catalyst. Moreover, a Zn-Zn bond with a bond length of 0.01 to 3.0 Å and a bond length of 0.1 to 5.0 Å are formed between the two. The Zn-Co bond of Å is closely connected through the interaction between metals, forming a more stable coordination environment, reducing the risk of deactivation of the catalyst due to ligand dissociation; therefore, due to the synergistic effect of the double metal cyanide catalyst DMC and the zinc pyridine carboxylate complex, more zinc active sites are exposed on the surface of the composite catalyst of the present invention, and cobalt active sites are provided during the composite process. The combination of the two metal active sites ultimately has the characteristics of high selectivity and high activity; the selectivity is reflected in the polycarbonate content being above 98.0%, and having a small molecular weight distribution, which is less than 1.5; the high activity means that the induction time of the composite catalyst of the present invention can be shortened to 2 h, and the catalytic activity can reach 480 g / cm2 in 4 h. polyment / g cat The catalyst activity increased steadily from 4 h to 12 h, and the catalytic activity could reach 510 g / cm2 in 12 h. polyment / g cat It can achieve an extremely high propylene oxide conversion rate of more than 95% in the low-temperature (30-75°C) catalytic carbon dioxide copolymerization reaction while ensuring a high carbonate content, significantly shortening the polymerization reaction time, so that the product has a high carbonate content, high molecular weight, high conversion rate and low by-product content, solving the problem that the existing polypropylene carbonate cannot take into account both high conversion rate and high carbonate content, as well as the problem of too long production process time, and is very suitable for industrial production.
[0054] (2) The present invention adopts a high-temperature inert gas atmosphere reaction to prepare the composite catalyst. Under this condition, the two metals in the zinc pyridine carboxylate and the bimetallic catalyst are more likely to form active sites, thereby exerting a synergistic effect, making the catalyst more selective and active. In particular, for the two types of catalysts, the interaction between the metals can be enhanced under an inert gas, thereby improving the structural stability of the catalyst. Compared with other preparation methods, the high-temperature gas atmosphere reaction of the present invention can obtain finer catalyst particles, smaller catalyst particle size and more excellent synergistic effect, so that the catalyst has more efficient and stable catalytic performance in subsequent polymerization reactions.
[0055] (3) In the zinc pyridine carboxylate complex prepared by the present invention, the zinc ion is usually in the central position in the zinc pyridine carboxylate complex, and is tightly bound to the carboxylate radical and the pyridine radical through coordination bonds. This coordination structure helps to enhance the catalytic activity of zinc, and it can provide a stable coordination environment and an optimized electronic structure. When the zinc pyridine carboxylate is further compounded with a bimetallic catalyst, a synergistic effect can be formed between them, and this synergistic effect can further accelerate the reaction rate and improve the selectivity.
[0056] (4) The method for preparing the zinc pyridine carboxylate complex of the present invention comprises the following steps: selecting a zinc source treated with hydrochloric acid to form a specific zinc precursor, subjecting the zinc precursor to a reflux reaction with a mixed solution of two pyridine carboxylic acids with different electronic groups, and then drying the mixture at high temperature to obtain zinc pyridine carboxylate with two functional groups. The above unique preparation processes complement each other to synthesize a high-purity zinc pyridine carboxylate complex with functional groups having different electronic characteristics. Among them, different electronic groups are used to react with the zinc source to form a zinc pyridine carboxylate complex with different electronic groups. The introduction of electron-donating and electron-withdrawing groups during the synthesis of the complex can significantly change the electronic structure of the zinc pyridine carboxylate complex, forming a diversified charge distribution and energy band structure. The diversity of the electronic structure can enable the complex to be better composited with the bimetallic catalyst, exposing more active sites on the catalyst surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 The XRD pattern of chloro-methyl-zinc pyridine carboxylate prepared in Example 1;
[0058] Figure 2 The WXRD pattern of the bimetallic catalyst prepared in the present invention;
[0059] Figure 3 This is the WXRD pattern of the composite catalyst prepared in Example 11. DETAILED DESCRIPTION
[0060] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0061] The detection method of the present invention is as follows:
[0062] Elemental composition of composite catalyst:
[0063] The elemental composition of the composite catalyst was analyzed by elemental analysis: the elemental analysis was measured using Vario Macro Cube-M336 equipment produced by Elementar Company of Germany.
[0064] Catalyst WRXD spectrum and chemical bond length test method: Wide-angle X-ray diffraction (WXRD) spectrum and data were obtained by measuring with Rigaku's Ultima IV.
[0065] Specific surface area test method: The Quantachrome automatic gas adsorption system (AUTOSORB-1-C) of the full adsorption instrument is used for detection, and the specific surface area is calculated using the BET technology N2 adsorption curve. Before the test, the catalyst is treated at 200℃ under vacuum for 1 hour to prevent dust or water adsorbed in the pores from affecting the test results.
[0066] Average volume particle size test method: The average volume particle size is measured by Nicomp 380 ZLS equipment produced by PSS Company of the United States. Before the measurement, the solid powder is dispersed with deionized water and the suspension is broken up with ultrasound.
[0067] Example 1
[0068] Preparation of zinc pyridine carboxylate complex:
[0069] (1) Add 13.63 g zinc chloride to 50 mL dilute hydrochloric acid solution (pH of dilute hydrochloric acid solution = 5) and stir at 30 °C for 2 h to form a zinc hydrochloric acid solution;
[0070] (2) Add 2.46 g of 4-chloro-2,6-pyridinedicarboxylic acid and 1.81 g of 4-methyl-2,6-pyridinedicarboxylic acid into 50 mL of deionized water and stir evenly at room temperature to form a pyridinecarboxylic acid mixed solution;
[0071] (3) adding the prepared zinc hydrochloric acid solution to the pyridine carboxylic acid mixed solution at a rate of 30 drops / min. After the addition, the reaction solution was heated at 100°C and refluxed for 6 hours. During the reflux heating process, stirring was continued at a rate of 400 r / min to ensure the formation of the pyridine carboxylic acid zinc complex.
[0072] (4) After the reaction is completed, the mixture is cooled to room temperature, crystals are gradually precipitated, and the crystals are washed and dried to obtain a zinc pyridinecarboxylate complex intermediate containing crystal water;
[0073] (5) removing crystal water from the zinc pyridine carboxylate complex intermediate at a high temperature of 150° C. to obtain the chloro-methyl-zinc pyridine carboxylate complex, which is retained for later use.
[0074] The zinc pyridine carboxylate complex prepared in Example 1 was subjected to elemental analysis by elemental analysis. The elemental analysis results (%) of the chloro-methyl-zinc pyridine carboxylate complex were: C, 39.60; H, 3.76; Cl, 7.56; N, 5.90; O, 20.69; Zn, 22.48. The WXRD spectrum of the zinc pyridine carboxylate complex prepared in Example 1 is shown in FIG. Figure 1 As shown, for chloro-methyl-zinc pyridine carboxylate, its characteristic peaks appear at 2θ=10.7, 13.3, and 18.8°. After the interaction between the electron-withdrawing group and the electron-donating group, the characteristic peak intensity is higher and sharper, which further proves that the electron-withdrawing group and the electron-donating group can improve the crystallinity of the zinc pyridine carboxylate particles. Combined with the ratio of Cl and C in the elemental analysis, it is proved that the electron-withdrawing group and the electron-donating group react well to obtain the chloro-methyl-zinc pyridine carboxylate complex, and its structure is shown below:
[0075]
[0076] Examples 2-10 refer to the preparation method and detection method of the zinc pyridine carboxylate complex of Example 1, and the specific raw materials and process parameters are shown in Table 1.
[0077] Table 1 Preparation parameters of zinc pyridine carboxylate complexes of Examples 1-10
[0078]
[0079] Table 1 Preparation parameters of zinc pyridine carboxylate complexes of Examples 1-10
[0080]
[0081] The double metal cyanide catalyst DMC of the present invention adopts a traditional preparation method, and can be prepared specifically according to the following steps:
[0082] Dissolve 1.2 g K3[Co(CN)6] in 50 mL aqueous solution to prepare a solution, and dissolve 4.8 g ZnCl2 in 60 mL water and 60 mL tert-butanol mixed solution to prepare a solution. Under strong stirring, add K3[Co(CN)6] solution drop by drop into ZnCl2 solution at a rate of 30 drops / minute. After the addition is completed, maintain strong stirring to allow the mixed solution to continue to react for 2 h. The resulting white suspension is washed with a mixed solution of 50 mL water and 50 mL tert-butanol under strong stirring until the potassium ion detection reagent Na3Co(NO2)6 can no longer detect K in the mixed solution. + The mixed solution was filtered and then placed in a vacuum oven at 90°C to dry overnight. The obtained DMC (Zn3[Co(CN)6]2: ZnCl2•1.5 tBuOH·2 H2O) catalyst solid powder is light yellow. The WXRD spectrum of the prepared DMC catalyst is as follows Figure 2 As shown, for the bimetallic catalyst, its characteristic peaks appear at 2θ=16.8,19.28°, which is consistent with the characteristic peak position of the structure Zn3[Co(CN)6]2: ZnCl2•1.5 t-BuOH·2 H2O, and belongs to a zinc-cobalt bimetallic catalyst.
[0083] Embodiment 11
[0084] Composite catalyst preparation method:
[0085] 20 mL of toluene, 10 mL of ethanol, and 10 mL of deionized water were added to a stirring bar, and then 1 mol of the chloro-methyl-pyridinecarboxylic acid zinc complex in the above Example 1 and 10 mol of DMCZn3[Co(CN)6]2: ZnCl2•1.5 t-BuOH·2 H2O were added to a high-pressure reactor. The high-pressure reactor was then pressurized to 0.8 MPa under argon, and then ultrasonic dissolution was performed for 10 min. After the dissolution was completed, the reaction was carried out at 100°C for 24 h.
[0086] After the reaction is completed, the mixture is cooled to room temperature, and the suspension is washed with 50 mL of acetone. After washing three times, the mixture is filtered to obtain a white solid, which is then dried in a vacuum drying oven to obtain a chloro-methyl-pyridine carboxylic acid zinc / DMC composite catalyst. The WXRD spectrum of the obtained chloro-methyl-pyridine carboxylic acid zinc / DMC composite catalyst is shown in FIG. Figure 3 As shown, it can be seen intuitively that the chloro-methyl-zinc pyridine carboxylate / DMC composite catalyst system has the crystal peak characteristics of chloro-methyl-zinc pyridine carboxylate and DMC catalyst. For the chloro-methyl-zinc pyridine carboxylate catalyst, its characteristic peaks appear at 2θ=10.7, 13.3, 18.8°; while for the DMC catalyst, its characteristic peaks appear at 2θ=16.8, 19.28°. In the WXRD curve of the chloro-methyl-zinc pyridine carboxylate / DMC composite catalyst, the crystal peaks of chloro-methyl-zinc pyridine carboxylate and DMC catalyst are obvious and the peak shape is very sharp, indicating that the chloro-methyl-zinc pyridine carboxylate and DMC catalyst have been completely composited, and the composite process of the two has no effect on the crystal morphology of the catalyst particles.
[0087] The preparation process parameters of the composite catalysts of Examples 11-20 are shown in Table 2, and the performance parameters of the composite catalysts tested according to the detection method of the present invention are shown in Table 3.
[0088] Table 2 Process parameters for preparing composite catalysts of Examples 11-20
[0089]
[0090] Table 3 Performance parameters of composite catalysts of Examples 11-20
[0091]
[0092] Table 3 Performance parameters of composite catalysts of Examples 11-20
[0093]
[0094] Comparative Example 1
[0095] The preparation method and detection method of Example 1 are referred to, except that methyl pyridine carboxylic acid is used instead of 4-chloro-2,6-pyridinedicarboxylic acid and 4-methyl-2,6-pyridinedicarboxylic acid of the present invention to prepare the pyridinecarboxylic acid zinc coordination compound. The method for preparing the composite catalyst is referred to Example 11, and the specific parameters are shown in Table 4.
[0096] Comparative Example 2
[0097] The preparation method and detection method of Example 1 are referred to, except that the zinc source is not acidified with dilute hydrochloric acid, but is directly added to the pyridine mixed solution to prepare the pyridine carboxylic acid zinc complex. The method for preparing the composite catalyst is referred to Example 11, and the specific parameters are shown in Table 4.
[0098] Comparative Example 3
[0099] The preparation method and detection method of Example 1 are referred to, with the only difference being that the zinc pyridinecarboxylate complex is not subjected to the operation of removing crystal water, and is then directly composited with the subsequent bimetallic catalyst for preparation. The method for preparing the composite catalyst is referred to Example 11, and the specific parameters are shown in Table 4.
[0100] Comparative Example 4
[0101] The preparation method and detection method of Example 1 are referred to, except that the zinc hydrochloric acid solution is not added dropwise to the zinc pyridine carboxylate mixed solution, but is directly poured therein to prepare the zinc pyridine carboxylate complex. The method for preparing the composite catalyst refers to Example 11, and the specific parameters are shown in Table 4.
[0102] Comparative Example 5
[0103] The zinc pyridinecarboxylate complex prepared in Example 1 was used to prepare a composite catalyst by referring to the preparation method and detection method of Example 11. The only difference was that the gas atmosphere reaction was not used in the preparation of the composite catalyst, and the composite catalyst was prepared directly under air conditions. The specific parameters are shown in Table 4.
[0104] Comparative Example 6
[0105] Referring to the preparation method and detection method of Example 11, the zinc glutarate in patent CN101979424 A and the DMC catalyst prepared by the present invention are directly used to prepare a composite catalyst, and the specific parameters are shown in Table 4.
[0106] Comparative Example 7
[0107] The zinc pyridine dicarboxylate complex catalyst in CN112679718 A was prepared by referring to the method in the patent, and then a composite catalyst was prepared with the DMC catalyst prepared by the present invention by referring to the preparation method of Example 11 to obtain a composite catalyst. The specific parameters are shown in Table 4.
[0108] Table 4 Process parameters for preparing composite catalysts in Comparative Examples 1-8
[0109]
[0110]
[0111] Application examples and comparative application examples
[0112] The composite catalysts prepared in the above Examples 11-20 and Comparative Examples 1-7 were used to prepare propylene oxide-carbon dioxide copolymers according to the following synthesis method, which were respectively recorded as Application Examples 1-10 and Comparative Application Examples 1-7. Specific parameters are shown in Table 5.
[0113] A rotor and 0.2 g of a composite catalyst (the composite catalyst is derived from the corresponding embodiment and the corresponding comparative example) were added to a 60 mL high-pressure reactor. The mixture was dried at 30°C for 2 h under vacuum conditions, cooled to room temperature, 20 mL of purified propylene oxide was added, and carbon dioxide was charged to make the pressure in the reactor reach 3.0 MPa. After continuous reaction at 70°C with a stirring speed of 500 rpm for 12 h, the reactor was removed, cooled to room temperature, unreacted carbon dioxide was discharged, the product in the reactor was taken out, unreacted monomers were removed by vacuum, and the obtained product was washed with a mixed solution of dichloromethane and methanol, and dried to obtain a copolymer of carbon dioxide and propylene oxide. The conversion rate of propylene oxide and the catalytic activity of the catalyst can be calculated by weighing and testing.
[0114] Specific method and calculation formula for propylene oxide conversion rate: propylene oxide conversion rate % = copolymer mass × 0.569 / propylene oxide mass × 100%
[0115] Carbonate group content detection and calculation method: The molar fraction of carbonate structural units in epoxy compound-carbon dioxide copolymer resin is determined by nuclear magnetic resonance hydrogen spectrum 1 H-NMR, according to the analytical method described in CN111349224A at
[0057] -
[0068] .1 The molar fraction of the carbonate group content was determined by H-NMR (Bruker, DPX400, 400 MHz; pulse program zg30, waiting time d1:10 s, 64 scans). In each case, the sample was dissolved in deuterated chloroform. 1 The relevant resonances in H-NMR (based on TMS=0 ppm) are as follows: 5.0 ppm and 4.2 ppm belong to the proton peaks of the methine and methylene groups on the polycarbonate group, 4.9 ppm, 4.5 ppm and 4.1 ppm belong to the proton peaks of the methine and methylene groups in the five-membered ring carbonate, and 3.5-3.8 ppm belong to the proton peaks of the ether group. The capital letter A plus a numerical subscript represents the integrated area of the peak at a certain ppm on the nuclear magnetic hydrogen spectrum. A is the abbreviation of Area in English. For example, A5.0 represents the integrated area of the peak at 5.0 ppm. According to the crude copolymer product 1 The integrated area of the H-NMR spectrum and its related proton peaks defines the ratio (molar ratio) of carbonate groups in the copolymerization reaction (F CO2 ) is calculated as follows:
[0116] F CO2 =(A 5.0 +A 4.2 -2×A 4.5 ) / [(A 5.0 +A 4.2 -2×A 4.5 )+A 3.5 ]×100%.
[0117] By-product content detection and calculation method: The by-product is a cyclic small molecule propylene carbonate, and its weight is expressed by Wcc%. In the carbonate group content detection method, the chemical environment corresponding to each peak is known, so Wcc%=102A 4.5 / [102(A 5.0 +A 4.2 -2A 4.5 +A 1.5 )+58A 3.5 ], where 102 is the molecular weight of propylene carbonate and polycarbonate groups, and 58 is the chemical molecular weight of the polyether structure.
[0118] Number average molecular weight detection method and molecular weight distribution detection method: measured by GPC, the specific test conditions are: gel chromatography column is PLgelMixed-C column (300mm×4.5mm, 5μm); column temperature is 40℃; mobile phase is tetrahydrofuran, flow rate is 1mL / min; injection volume is 100μL; analysis time is 20min. The number average molecular weight and molecular weight distribution data can be obtained.
[0119] Table 5 Process parameters and performance parameters of the composite catalysts used in the examples of the present invention and the comparative examples for preparing propylene oxide-carbon dioxide copolymers
[0120]
[0121]
[0122] From the data of Examples 11, 14, and 19 in Table 2, it can be seen that in the synthesis and preparation process of zinc pyridine carboxylate and bimetallic catalyst synthesized for different substituted groups of chlorine substitution and methyl substitution on the benzene ring, when the temperature is reduced and the pressure of the reactor is reduced, the average volume particle size of the synthesized composite catalyst becomes larger, and the specific surface area of the catalyst decreases, so the catalytic effect of the formed composite catalyst is reduced. From Application Examples 1, 4, and 9 in Table 5, it can be seen that the higher the composite temperature and the greater the pressure, the higher the catalyst activity, the best catalyst conversion rate and carbonate content, and the lower molecular weight distribution.
[0123] Since the catalyst of comparative example 5 was not successfully compounded, the two still belonged to a simple physical mixing state. It can be seen from Table 2 that the mixed catalyst has a low activity in comparative application example 5. The reason is that the catalyst has not been subjected to nitrogen / argon pressure treatment to complete the compounding process, but has only undergone simple physical mixing. Therefore, in the application, the mixed catalyst only plays the role of zinc pyridine carboxylate and the bimetallic catalyst, but does not form a synergistic effect, and does not form a Zn-Zn bond and a Zn-Co bond, and the active center is not formed, so the activity is low. In the catalyst preparation process, if the composite ratio of the two components of the present application is exceeded, the synergistic effect of the present invention cannot be achieved. In extreme cases, only zinc pyridine carboxylate catalyst or bimetallic catalyst exists, and the catalyst activity is low and does not have selectivity. Only polyether polymers can be formed under the bimetallic catalyst, and the activity is low under the zinc pyridine carboxylate catalyst. Therefore, the composite catalyst prepared within the range ratio of the present application can keep the zinc pyridine carboxylate and the bimetallic catalyst synergistic, so that the catalyst activity and selectivity reach the best state.
[0124] From the data of Examples 11, 15, and 18 in Table 2, it can be seen that in the synthesis and preparation process of zinc pyridine carboxylate and bimetallic catalyst synthesized with different substituent groups of chlorine substitution, methyl substitution, and phenyl substitution on the benzene ring, the change of the substituent will reduce the bond length in the composite catalyst prepared by zinc pyridine carboxylate, but the average volume particle size and specific surface area are mainly affected by the temperature and pressure changes during the composite process. From Application Examples 1, 5, and 8 in Table 5, it can be seen that for different polymerization temperatures and polymerization times, more than 98% of the product can be obtained at a milder polymerization temperature, but the ester content and distribution are significantly reduced, and the conversion rate is also reduced when the polymerization time is shortened by half, but the overall situation is above 95%, which shows that the catalyst we prepared has a short induction time and can quickly form the target polymer.
[0125] From the data of Application Example 1 in Table 5, Comparative Application Example 1, Example 11 in Table 4 and Comparative Example 1 in Table 2, it can be seen that the catalytic efficiency of the composite catalyst formed by different substituent groups is lower than that of the same substituent groups, and the catalyst activity is reduced. The conversion rate of the formed composite catalyst is reduced by 40% in the polymerization reaction, the ester content is reduced, and the molecular weight distribution is broadened, and the performance of the formed polymer product is reduced. Therefore, the activity of the zinc pyridinecarboxylate catalyst formed by the combination of the electron-withdrawing group and the electron-donating group used in the present invention is improved, and this condition is a necessary condition for the preparation of the composite catalyst.
[0126] From the data of Example 11 and Comparative Examples 2-4 in Table 4 and Table 2, it can be seen that in the process of preparing zinc pyridine carboxylate, the operation requirements for various aspects are relatively high. Once the preparation is not carried out as required, the formation of the complex will lead to uneven formation of the complex in the process of forming zinc pyridine carboxylate, especially for the addition of two different types of electronic groups, if the dropwise addition reaction is not carried out as required, it will lead to the formation of only one electronic group product, or the competitive reaction will produce deviations, and the formation of products with different substituted groups will be less, which will affect the preparation of the subsequent composite catalyst, affect the catalytic activity of the composite catalyst, and also cause the composite catalyst formed to be unstable, and the active group does not play a role in the polymerization process. The data of Application Example 1 and Comparative Application Examples 2-4 in Table 5 can support our experimental conclusions.
[0127] From the comparison between Application Example 5 and the embodiment in Table 5, the composite catalyst formed in Comparative Example 5 was not successfully composited due to the lack of pressurization. Therefore, in Application Comparative Example 5, zinc pyridine carboxylate and DMC in the composite catalyst each played a role without synergistic effect, the activity of the generated catalyst was reduced, and the ester content of the formed polymer product was reduced. The pressurization condition in the composite catalyst is a necessary condition, which affects the formation of the synergistic effect of the composite catalyst.
[0128] From Table 5, compared with Example 1, the zinc carboxylate catalysts used in Comparative Examples 6-7 are different. In Example 6, zinc glutarate catalyst is used, and in Example 7, zinc pyridine carboxylate catalyst without electron groups is used to form a composite catalyst with DMC. Although the carbonate content of the composite catalyst formed in Comparative Example 7 reaches 98%, the high conversion rate is sacrificed, and the conversion rate is only 35%. The catalyst selectivity is good but the activity is low. In Comparative Example 6, both the ester content and the conversion rate are low. Therefore, the composite catalyst of the present invention can quickly initiate the polymerization reaction, and both the selectivity and activity remain highly stable.
[0129] In summary, it can be seen from the above embodiments and comparative data that the preparation method of the present invention comprises a zinc pyridine carboxylate complex and a bimetallic cyanide catalyst DMC of a specific ratio and structure, and a synergistic effect occurs between the bimetallic cyanide catalyst DMC and the zinc pyridine carboxylate complex, and the bimetallic cyanide catalyst itself contains the synergistic effect of two metals, and the introduction of a zinc pyridine carboxylate complex can further enhance the synergistic effect between cobalt and zinc, and the electron transfer and interaction between different metals can improve the catalyst activity and selectivity, and the interaction between the metals is closely connected, and the tightness of this structure can reduce the structural changes and agglomeration of the catalyst during the catalytic process, and the composite of the bimetallic catalyst and the zinc pyridine carboxylate complex can also form a more stable coordination environment, reducing the risk of deactivation of the catalyst due to ligand dissociation. Zinc pyridine carboxylate is an important component in the composite catalyst, and the N and O atoms in its ligand can form a stable complex with the zinc metal center, and in the process of compounding with the bimetallic catalyst, there is electron transfer between cobalt, zinc metal and zinc pyridine carboxylate, and these electron transfer sites can affect the charge distribution and electronic structure of the catalyst, thereby improving the catalytic performance of the catalyst. The composite catalyst of the present invention comprises a zinc pyridine carboxylate complex and a double metal cyanide catalyst DMC in a molar ratio of 1:1-60. The zinc pyridine carboxylate complex has both an electron-withdrawing group and an electron-donating group, has the characteristics of high selectivity and high activity, and the catalytic activity can reach 510 g / cm2 in 12 h. polyment / g cat It can achieve extremely high propylene oxide conversion rate in the low temperature (30-75°C) catalytic carbon dioxide copolymerization reaction, significantly shorten the polymerization reaction time, and make the product have high carbonate content, high molecular weight, high conversion rate and low by-product content, which is suitable for industrial production.
[0130] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite catalyst containing a zinc pyridine carboxylate complex, characterized in that: The composite catalyst comprises a zinc pyridine carboxylate complex and a double metal cyanide catalyst DMC, wherein the molar ratio of the zinc pyridine carboxylate complex to the double metal cyanide catalyst DMC is 1:1-60, and the structural formula of the zinc pyridine carboxylate complex is as shown in Formula 1: Formula 1, Wherein, R1 is an electron withdrawing group selected from -CF3, -CN, -F, -Cl, -Br, -I; R2 is an electron donating group selected from -O-, -NHR3, -NH2, -OH, -OR4, -R5, -Ph, wherein R3, R4, R5 are any alkyl groups; The composite catalyst is prepared by adding a zinc pyridine carboxylate complex, a double metal cyanide catalyst DMC and a mixed solvent into a high-pressure reactor at one time for dissolution, and reacting in a nitrogen / argon atmosphere. The mixed solvent is a mixed solvent comprising a polar solvent and a non-polar solvent.
2. The composite catalyst according to claim 1, characterized in that The composite catalyst has a Zn-Zn bond with a bond length of 0.01 to 3.0 Å and a Zn-Co bond with a bond length of 0.1 to 5.0 Å.
3. The composite catalyst according to claim 1, characterized in that The composite catalyst has the following elemental composition by mass percentage: Zn 10-30%, Co 5-20%, C 30-40%, N 4-20%, O 10%-20%, and other substituent elements 1-20%.
4. The composite catalyst according to claim 1, characterized in that The structural formula of the double metal cyanide catalyst DMC is: Zn3[Co(CN)6]2:x ZnCl2•y t-BuOH·z H2O, wherein the x value ranges from 0.5 to 2.0, the y value ranges from 0.9 to 3.0, and the z value ranges from 1.0 to 3.
5.
5. The composite catalyst according to claim 1, characterized in that The molar ratio of the zinc pyridine carboxylate complex to the double metal cyanide catalyst is 1:5-30.
6. A method for preparing the zinc pyridinecarboxylate complex composite catalyst as claimed in claim 1, characterized in that: In the preparation of the composite catalyst, the molar ratio of the zinc pyridine carboxylate complex to the double metal cyanide catalyst DMC is 1:1-60, the reaction temperature is 20-150°C, the reaction time is 12-38 h; and the pressure of the nitrogen / argon atmosphere is 0.2-1 MPa.
7. The preparation method according to claim 6, characterized in that: The preparation method of the zinc pyridine carboxylate complex is: (1) dissolving a zinc source in dilute hydrochloric acid and stirring to obtain a zinc hydrochloric acid solution; (2) dissolving a pyridine carboxylic acid containing an electron-withdrawing substituent and a pyridine carboxylic acid containing an electron-donating substituent in deionized water to form a pyridine carboxylic acid mixed solution; (3) slowly adding the zinc hydrochloric acid solution dropwise to the pyridine carboxylic acid mixed solution to perform a reflux reaction; (4) cooling, precipitating crystals, washing, and drying to obtain a zinc pyridinecarboxylate complex intermediate containing crystal water; (5) removing crystal water from the zinc pyridine carboxylate complex intermediate at a high temperature of 110 to 150° C. to obtain the zinc pyridine carboxylate complex; The zinc source is selected from any one of zinc chloride, zinc sulfate (ZnSO4), zinc chlorate [Zn(ClO3)2], zinc nitrate [Zn(NO3)2], zinc acetate [Zn(OAc)2], zinc oxide and zinc hydroxide; The dilute hydrochloric acid refers to an aqueous solution of HCl with a pH value between 0 and 5; The electron-withdrawing substituent group is selected from -CF3, -CN, -F, -Cl, -Br, -I; The electron-donating substituent group is selected from -O-, -NHR3, -NH2, -OH, -OR4, -R5, -Ph, wherein R3, R4, R5 are any alkyl groups.
8. Use of the composite catalyst according to any one of claims 1 to 5 or the composite catalyst prepared by the preparation method according to any one of claims 6 to 7 in preparing a copolymer of carbon dioxide and propylene oxide.
9. The use according to claim 8, characterized in that: The composite catalyst is one or more of methyl-chloro-zinc pyridine carboxylate / DMC, bromo-ethoxy-zinc pyridine carboxylate / DMC, chloro-ethyl-zinc pyridine carboxylate / DMC, and bromo-methoxy-zinc pyridine carboxylate / DMC.
10. The use according to claim 8, characterized in that: The method for preparing a copolymer of carbon dioxide and propylene oxide is as follows: adding a composite catalyst whose mass is 0.1-5% of the mass of the reaction monomer propylene oxide into a reaction kettle, drying at 30-75°C for 2-24 hours under vacuum conditions, cooling to room temperature, adding purified propylene oxide, charging with carbon dioxide to make the pressure in the kettle reach 1.0-6.0 MPa, reacting continuously at 30-75°C and a stirring speed of 100-500 rpm for 4-12 hours, removing the reaction kettle, cooling to room temperature, discharging unreacted carbon dioxide, taking out the product in the kettle, removing unreacted monomers under vacuum, washing the obtained product with a mixed solution of dichloromethane and methanol, and drying to obtain a copolymer of carbon dioxide and propylene oxide.
Citation Information
Patent Citations
Zinc hydroxy acid complex catalyst for copolymerization of carbon dioxide and propylene oxide and preparation method
CN101759849B
Preparation method and application of composite catalyst for synthesis of carbon dioxide copolymer
CN101979424A
Method for continuously producing polycarbonate-polyether polyol in channelization mode through liquid phase method
CN111349224A
A polypropylene carbonate and its preparation method
CN113185684B
Composite catalyst, carbon dioxide-based copolymer and preparation method and application thereof
CN114591501A
